Situation Report: Romania, 15 November 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Two Labor Bills Approved Prime Minister Manescu Visits Iraq The 1976 Bucharest International Fair Joint Commission on Economic Relations with Iraq Meets Romania Reaches Textile Agreement with Common Market